InterPlay: Performing on a High- Tech Wire (Collaborative, Real- Time, Distributed, Surrealistic Cinema). - Miklavcic, Elizabeth Ann; Miklavcic, Jimmy (Journal of the Utah Academy of Sciences, Arts & Letters, 2010)
This paper will describe the InterPlay form and discuss its process and structure through the investigation of eight InterPlay performances. It will analyze some of the issues that have been encountered and surmounted and those that require continued examination. It will also discuss subjects such as distributed collaboration, communications, production elements, real and virtual venues, and the layered development of works within this innovative art form.